Hypertelorism-hypospadias Syndrome (Opitz Syndrome) - Marçallo, Francisco Antônio; Pilotto, Rui Fernando; Petrelli, N. Eros (Acta Biológica Paranaense, 1984)
Hypertelorism-hypospadias Syndrome (Opitz Syndrome)